APPROPRIATE TECHNOLOGY: TECHNOLOGY FOR SUSTAINABLE DEVELOPMENT - Loayza P., Jorge (2002)
The present article analyzes the role of technology in relation to the economic development and the environment. for the case of developing countries. One considers the adoption of "adequate technology", that is the most advisable technology for a poor country, which must be the result of an ample analysis and discussion by all the sectors involved in the decision making and must comprise of the Plan of Sustainable Development of each country. The adoption of this type of technology will enable the creation of jobs, the protection of the environment, the international trade and the economic development.